Incorporation of Bulky and Cationic Cyclam‐Triazole Moieties into Marimastat Can Generate Potent MMP Inhibitory Activity without Inducing Cytotoxicity. Issue 3 (12th June 2013) - Yu, Mingfeng; Lim, Ngee H.; Ellis, Samantha; Nagase, Hideaki; Triccas, James A.; Rutledge, Peter J.; Todd, Matthew H.
Abstract The synthesis and matrix metalloproteinase (MMP) inhibitory activity of a cyclam–marimastat conjugate and its metal complexes are described. The conjugate, synthesized with a copper(I)‐catalyzed Huisgen 1, 3‐dipolar cycloaddition ("click" reaction), contains two zinc‐binding groups (ZBGs). The metal complexation behavior with copper(II) and zinc(II) was investigated using UV/Vis spectrophotometry and 1H NMR spectroscopy, respectively, demonstrating that the first equivalent of the metal ion was chelated by the cyclam‐triazole moiety rather than the hydroxamic acid site. Thus, the corresponding mononuclear metal–cyclam complexes were successfully prepared with one equivalent of the metal salt. Both the cyclam–marimastat conjugate and its metal complexes exhibited slightly reduced potency against MMP‐1, but essentially identical inhibitory activity against MMP‐3. The conjugate and its metal complexes displayed little or no cytotoxicity, further supporting their potential suitability for imaging MMP localization and activity. To the best of our knowledge, this is the first report that describes the incorporation of metal complexes into an MMP inhibitor without influencing the preexisting ZBG, and the first report of the evaluation of structures containing more than one ZBG as MMP inhibitors.